The involvement of male homosexuals with mainstream newspapers' reporting of homosexuality / Mohd Shahnawi Muhmad Pirus - Muhmad Pirus, Mohd Shahnawi (2017)
The contributory factors to male homosexuals' (MH) involvement with mainstream newspapers reporting of homosexuality was observed on news content representation including the reporting criterion and its consistency to be reported to the audiences, triggering the public interest in receiving information and advocating themselves towards a guided living culture. This study was guided with two theories; (i) Uses and Gratifications Theory, and (ii) Social Judgment Theory following a series of content analysis on newspapers reporting of homosexuality that was conducted to understand how it was presented. Using a qualitative approach with phenomenology and popular culture paradigms, informants of male homosexuals from the non-governmental organization were selected randomly through the purposive and judgmental sampling strategies. All data were collected from in-depth interviews and content analysis procedures and analyzed by using thematic analysis and constant comparison strategy. It was disclosed such news reporting became a platform for the male homosexuals to be alert with current updates pertaining to homosexuality issues that established involvement. The inclination in getting involved among male homosexuals' readers with news reporting of homosexuality was also factored by the message conveyance on content delivery, news themes and overall reporting that strongly associated with the public awareness on issues of safe sex messages and crimes. In overall, this study had managed to observe on the role of mainstream mass media in Malaysia as a platform in disseminating the government agenda including to understand the possible factor that generated MH involvement as active audience affecting on their attitude and behavioral change induced by ego involvement.